The Organisation of University Libraries - Mazić, Bogoljub (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
I feel very honoured to address you about the organization of modern university libraries. I have been asked to talk about the reorganization of library functions in a modern university, and I am mainly going to describe what is happening in the UK. I have also visited university libraries in the United States of America, France, Germany and Spain, and in some ways the position of those libraries is similar to the traditions of academic librarianship in Serbia. The United Kingdom position is markedly different. However, on my visits to other countries, colleagues there seemed very interested in the UK approach to library service, and indeed, in learning from us, and following our example. And, of course, on those visits, I wanted to see what I could learn from their example, just as I am with this visit to you.